PENINGKATAN KOMPETENSI GURU MELALUI PENERAPAN PENELITIAN TINDAKAN KELAS (PTK) DALAM PENDIDIKAN ISLAM - Emilia Susanti dan Dicki Hartanto Emilia Susanti dan Dicki Hartanto (State Islamic University Sultan Syarif Kasim, 2015)
The class action research can be defined as a type of scientific study or activity and method done by teacher/researcher in class by using actions to increase process and result of the study. Scientific is something that have scientific character and method of thinking paths, objective, rational, systematic based on fact to find, prove, develop and evaluate a knowledge. The action research is a network of stages (cycle) which consists of planning, action, observation and reflection that continuosly yields new cycle until the class action research is stopped. Professional competences stated that teacher task as profession covers educating, teaching, and training. Teaching meaned continues and develops life values. Teaching means to continue and develop science and technology. While training means developing skills of student. Professional teacher will be able to create changes in the quality of a real basic education. Then the change would hardly depend on to what is learning do and teacher thought of about education. Pedaegogic competence is the ability to manage study of educative participant. If it is related to strategy to teach, an instructor has philosophic confidence about teaching paying attention to reasoning of knowledge and experience, situation of personality and environmental as purpose of study entangling student and teacher.